Organic matter components and aggregate stability after the application of different amendments to a horticultural soil - Albiach, Remedios; Canet, Rodolfo; Pomares, Fernando; Ingelmo, Florencio (2017)
The effects of usual or recommended rates of application of five organic amendments (24 t/ha yr of MSW compost, sewage sludge, and ovine manure, 2.4 t/ha yr of commercial vermicompost, and 100 l/ha yr of a commercial humic acids solution) on the soil contents of organic matter, total humified substances, humic acids, carbohydrates and microbial gums, and the structural stability of aggregates were investigated. Four and five years after the: beginning of the experiment, significant increments in most of the parameters studied were found after the application of organic residues, whereas the two commercial amendments did not produce any significant change, suggesting that rates recommended by the producers and imposed by their high prices are too low to be useful. MSW compost yielded the highest increases, even if the amount of organic Matter applied as ovine manure was very similar. Organic matter and carbohydrates appeared to be the parameters most closely related to soil aggregate stability. (C) 2000 Elsevier Science Ltd. All rights reserved.